2022
DOI: 10.1111/1467-923x.13173
|View full text |Cite
|
Sign up to set email alerts
|

A Four‐Day Working Week: its Role in a Politics of Work

Abstract: From a fringe idea with limited wider support, the goal of a four-day working week has moved into the spotlight in contemporary policy debates. Indeed, a growing number of businesses have agreed to pilot a four-day working week. This article examines what the turn to this goal means for a politics of work. It argues that its adoption by business interests can dilute its impacts, while its stress in some radical circles can distract from other pressing goals such as higher wages and improvement in work's qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…'s (2022) case study of a 4‐day week for agile software development teams found this led to increased job satisfaction and productivity but was also associated with increased stress levels. Spencer's (2022, 402) critique uses a political lens and draws on claims by Marx and Keynes that societal progress involves ‘…extending “free time”’. He raises the challenge that businesses are only likely to accept a 4‐day working week if it raises productivity and thus, from a COR perspective, is a resource.…”
Section: Initial Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…'s (2022) case study of a 4‐day week for agile software development teams found this led to increased job satisfaction and productivity but was also associated with increased stress levels. Spencer's (2022, 402) critique uses a political lens and draws on claims by Marx and Keynes that societal progress involves ‘…extending “free time”’. He raises the challenge that businesses are only likely to accept a 4‐day working week if it raises productivity and thus, from a COR perspective, is a resource.…”
Section: Initial Resultsmentioning
confidence: 99%
“…However, Hedges' (1973) arguments on worker fatigue demand attention, given the health implications. Similarly, Delaney and Casey (2022) and Spencer (2022) point out a danger of a 4‐day week is that workers could be exploited (e.g. work intensification) unless the focus is on creating a new system of work that is enriching and adds to worker well‐being, rather than simply productivity outcomes.…”
Section: Initial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in work conditions are linked to employer expectations (Hayden, 2006). If there is no (proportional) reduction in the expected output, then higher intensity and more exhausting work are likely (Delaney and Casey, 2021; Spencer, 2022). This may have health implications and potentially reduce the value of non-work time.…”
Section: Introductionmentioning
confidence: 99%
“…Although working hours have been greatly reduced in many high-income countries since the 19 th century, particularly in Europe, the discussion about working hours remains topical, as can be seen by the recent debate about a 4-day working week ( 5 , 6 ). In South-East and East Asian countries, such as Japan, South Korea, and Taiwan, where working hours >48 hours per week are still widely prevalent, health concerns of such long working hours are an important topic of discussion ( 7 , 8 ).…”
mentioning
confidence: 99%